ANALISIS KESESUAIAN BUKU PESERTA DIDIK KELAS IV BERBASIS KURIKULUM 2013 - Bernadine Ajeng Indriasari (Universitas Katolik Musi Charitas, 2019)
The purpose of this research is to know students book of four grade students based on Curricullum 2013 on theme Pahlawanku subtheme Perjuangan Para Pahlawan on lesson four with basic competence, objective, indicator, learning activity, materials, tool and learning resources. Research method is descriptive method by analyze document is student book of four grade student based on Curricullum 2013 on theme Pahlawanku subtheme Perjuangan Para Pahlawan on lesson four and teacher book of four grade student based on Curricullum 2013. The analize revolves on the rule of Menteri Pendidikan dan Kebudayaan Nasional, an article discussing about the implementation of Curricullum 2013 and article from Badan Nasional Standar Pendidikan (BSNP) website. The result of this research are found that some kompetensi dasar less related. Indicator is too broad or too narrow. Purpose of learning is not according with the indicators. Less meaningfull learning activities. The material is too shallow. Also tools and learning that need to be adapted to the learning activities. As the conclusions, student bood of four grade student theme Pahlawanku subtheme Perjuangan Para Pahlawan on lesson four needs much improved with the discrepancies in its parts.